Peradaban Islam Pada Masa Pemerintahan Khulafaur Rasyidin - Fahira Iramadhania; Yuan Amelia Tri Ananda; Tri Hartanti; Zulham Zulham (Jurnal Sosial Humaniora dan Pendidikan, 2023)
During the leadership of Khulafaur Rasyidin, many achievements were recorded for Islamic civilization. As Muslims, we should study and take lessons from the progress they have achieved for Islam. This research discusses Islamic civilization that occurred during the reign of Khulafaur Rasyidin. Author’s focus aims to describe the government system of Khulafaur Rasyidin, the leadership of the caliph Abu Bakar Ash-Shiddiq, Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib. The method in this research is literature study and bibliographic annotation analysis using Publish or Perish, Google Scholar and digital libraries. Research results showed that Khulafaur Rasyidin was the intellectual successor of the Apostle, where the four Caliphs were close and friendly with the Messenger of Allah. Abu Bakar’s "Central" leadership means all power legislative, executive and yudicial powers are centered on the Caliph. During the time of Umar bin Khattab, who was known for being firm and brave, political conditions were stable, the leadership of Caliph Umar RA implemented the democratic principle of power, name guaranteeing equal rights for every cityzen. Uthman’s leadership was known to be generous and accomplished in rewriting the Koran which had been codified during Abu Bakr’s time. During Ali’s reign, he faced many upheavals. Ali bin Abi Talib’s intelligent leadership, one of his efforts was to advance the field of linguistics.